Bibliometric and visualized analysis of exercise and osteoporosis from 2002 to 2021 - Li, Fan; Xie, Weixin; Han, Yi; Li, Zhanchun; Xiao, Jie (Frontiers in Medicine, 2022)
ABSTRACT Background: Bibliometric analysis was designed to investigate a systematic understanding of developments in exercise and osteoporosis research over the past 20 years. Methods: Relevant publications from the Web of Science Core Collection were downloaded on April 26, 2022. CiteSpace, VOSviewer, and the online bibliometric analysis platform were used to conduct this scientometric study. Results: A total of 5518 publications were in 1202 academic journals with 137405 co-cited references in by 5637 institutions from 98 countries/regions. The country leading the research was the USA. The University of Melbourne was the most active institution. Osteoporosis International was the most productive journal concerning exercise and osteoporosis research. According to the burst references, “low-level vibration”, “high-frequency” and “resistance exercise” have been recognized as the hotspots research in the domain. The keywords co-occurrence analysis identified “skeletal muscle” “sarcopenia” and “mesenchymal stem cell” as the important future research directions. Conclusion: This study was the first comprehensive metrological and statistical analysis of exercise and osteoporosis research over the past 20 years. Our findings would provide guidance to understand the research frontiers and hot directions in the near future.